A case report of intraventricular tigecycline therapy for intracranial infection with extremely drug resistant Acinetobacter baumannii. Issue 31 (August 2017) - Fang, Yu-Qing; Zhan, Ru-Cai; Jia, Wei; Zhang, Bao-Qing; Wang, Jian-Jun
Abstract: Rationale: Intracranial infection with Acinetobacter baumannii is a tough problem due to the presence of multiresistance and drugs poor penetration through the blood brain barrier (BBB). Tigecycline is effective to cure A baumannii, but it can only be used intravenously which is also difficult to pass BBB. So, it will be a breakthrough if intraventricular (IVT) tigecycline is used in the clinical therapy. However, this treatment has been reported quite rarely until now. Patient concerns: We described a case of a 50-year-old male worker whose clinical futures were high fever and cerebral rigidity after neurosurgery. Diagnoses: Intracranial infection with extensive drug resistant (XDR) A baumannii . Interventions: The patient was treated with IVT tigecycline. Outcomes: The symptoms of intracranial infection disappeared. The temperature of this patient decreased to normal and cerebral rigidity disappeared. The cerebrospinal fluid culture became negative, with normal levels of white blood cell, glucose and chlorine. Lessons: IVT tigecycline therapy maybe effective to intracranial infection with XDR A baumannii . However, more studies will further demonstrate the therapeutic values of IVT tigecycline to intracranial infection, and not only restricted to A baumannii infections.